Análise da relação do patrimônio arquitetônico com a eficiência energética em edifícios históricos em Santa Maria, RS. - Alvorcem, Cândida Ianzer Viedo (2019)
Architectural heritage represents a material production as a way to express pastsocieties identity, it is also a way to connect with values predecessors users. Historical buildings represent an era culture and are an important research source. In this context, there are several considerations about energy efficiency and photovoltaic use to make this buildings more sustainable. These modifications also are aligned to current needs of reducing buildings environmental impact of. Thus, main objective of this work is to analyze relationship between architectural heritage and energy efficiency plus solar photovoltaic generation, using two historic buildings in Santa Maria, RS. First, a bibliographic review was carried out about energy efficiency and Brazilian laws related with public buildings, and solar photovoltaic generation. The methodology followed this steps: case studies selection and identification as a reference historical building, application of Brazilian law RTQ-C, prescriptive method in each building; design of PV system shadows considerate; comparative of results obtained and conclusions. As a results was obtained two building evaluation energy efficiency level, where it was noticed that both reach levels between a C and an E. These historical construction systems differ from todays constructions, which can negatively influence the classification of the efficiency level. Both Manoel Ribas School and Palace Dr. Astrogildo de Azevedo obtained level E in the envelope and reached level C as a General Label. As for shading analysis, Manoel Ribas School is not influenced by shading of the surroundings, since it is implanted in an isolated lot. Palacete Dr. Astrogildo de Azevedo as being inserted in dense urban environment, is greatly impaired due shadowing caused by surrounding buildings. Modules were installed in Manoel Ribas School rooftop, which would generate building most electrical energy demand (eighty-four percent). For Palace Dr. Astrogildo de Azevedo, modules arranged on the roof would reach sixteen percent of building demand. Some alternatives may be proposed so that integration of PV systems is possible, such as arrangement of modules only in places where they are not visible from facades, or even choice of another location for system deployment. It was possible to conclude that installation of a photovoltaic system in historical buildings would increase their energy efficiency,since both would present classification level B, but the architectural characteristics of the buildings and the visual impact of these could be impaired by designers making the analyzes prioritizing the generation of energy or minimal architectural influence. Changes in lighting and air conditioning systems are indicated to increase the classification of the level of energy efficiency, since they are the ones that can offer a lower cost of intervention and great benefit.